2016
DOI: 10.1108/md-11-2015-0537
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneur’s paternalistic leadership style and creativity

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 59 publications
8
91
2
1
Order By: Relevance
“…The scale's α reliability was 0.958. We controlled for respondents' gender, age, work experience, and education because of the potential influence of these individual characteristics on employee innovative behavior [73,74].…”
Section: Methodsmentioning
confidence: 99%
“…The scale's α reliability was 0.958. We controlled for respondents' gender, age, work experience, and education because of the potential influence of these individual characteristics on employee innovative behavior [73,74].…”
Section: Methodsmentioning
confidence: 99%
“…Followers of authentic leaders get more intrinsically motivated (Ilies et al, 2005), and through the intrinsic motivation caused by feeling meaningful and valuable, employees feel at liberty to engage in voice behaviors (Chen, Wang, & Lee, 2018) and speak out with new ideas. Dedahanov, Lee, Rhee, and Yoon (2016) suggested that moral leadership style facilitates employee voice which in turn impacts on creativity. Authentic leaders’ transparency and trust allow employees the freedom to innovate without fear of reprisal.…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
“…As regards innovation measures, the academic literature has considered R&D to be the first step in innovation and technological progress (Lerner and Wulf, 2007;Nekhili and Gatfaoui, 2013), because it is the initial stage in technological innovation that involves obtaining new knowledge applicable to the company's commercial requirements, which will eventually lead to new or improved products, processes, systems or services that can increase the company's sales and earnings. In addition to this, other measures have been used to measure innovation: Dedahanov et al (2016) consider new and innovative ideas; Allred and Swan (2004) and Chen et al (2017) believe that innovation should be measured by R&D intensity; new product development is the measure proposed by Yang and Li (2011); design and new technology is suggested by Griffith and Rubera (2014) and Shane (1993) proposes the number of patents per capita or the number of trademarks registered per capita.…”
Section: Research Hypothesesmentioning
confidence: 99%